Sejarah Peradaban Islam Dinasti Abbasiyah - Umi Nasikhah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Islamic civilization has played an important role in world history, with significant contributions in the fields of science, philosophy, architecture, and culture. Therefore, it is important to study and understand the history of Islamic civilization to understand its significant influence in the modern world. The Abbasid Dynasty was one of the golden periods in the history of Islamic civilization, with significant contributions in various fields. The Abbasid Dynasty was one of the dynasties that had a high civilization in the field of science, of course this was inseparable from the efforts made by the caliphs who led the government. Efforts continued to be made by translating foreign works that had previously experienced civilization in the fields of science and other fields. This article will discuss the history of the Abbasid Dynasty and its contributions to Islamic civilization.